Copper-catalyzed asymmetric hydrogenation of 2-substituted ketones via dynamic kinetic resolution. Issue 19 (30th April 2018) - Zatolochnaya, Olga V.; Rodríguez, Sonia; Zhang, Yongda; Lao, Kendricks S.; Tcyrulnikov, Sergei; Li, Guisheng; Wang, Xiao-Jun; Qu, Bo; Biswas, Soumik; Mangunuru, Hari P. R.; Rivalti, Daniel; Sieber, Joshua D.; et al.
Abstract : A new class of tunable heterophosphole dimeric ligands have been designed and synthesized. Abstract : A new class of tunable heterophosphole dimeric ligands have been designed and synthesized. These ligands have enabled the first examples of Cu-catalyzed hydrogenation of 2-substituted-1-tetralones and related heteroaryl ketones via dynamic kinetic resolution, simultaneously creating two contiguous stereogenic centers with up to >99 : 1 dr and 98 : 2 er. The ligand-Cu complexes were isolated and characterized by single crystal X-ray, and DFT calculations revealed a novel heteroligated dimeric copper hydride transition state.